Small States: Making the Most of Development Assistance, A Synthesis of World Bank Evaluation Findings - Independent Evaluation Group (Washington, DC: World Bank, 2012)
The Independent Evaluation Group (IEG) prepared this synthesis note as an input to the ongoing process surrounding the international agenda for Small States. Its purpose is to provide a perspective on some of the issues small states face through a review of World Bank experience with country and project assistance. The lessons and findings are drawn from IEG Country Assistance Evaluations and Project Performance Assessment Reports, as well as from IEG Reviews of Country Assistance Strategy Completion Reports and Project Implementation Completion Reports.